Ultrasound-guided modified subcostal transversus abdominis plane block and influence of recumbency position on dye spread in equine cadavers. (July 2021) - Freitag, Flavio A.V.; Amora, Dorli da S.; Muehlbauer, Eloisa; Dornbusch, Peterson T.; Machado, Marcello; Montiani-Ferreira, Fabiano; Prisco Farias, Edison L.; Valverde, Alexander; Duque Moreno, Juan Carlos
Abstract: Objective: To describe and evaluate an ultrasound-guided modified subcostal approach for the transversus abdominis plane (TAP) block in horse cadavers in lateral or dorsal recumbency. Study design: Prospective, experimental cadaveric study. Animals: Study of one preserved foal and eight fresh adult horse cadavers. Methods: The lateral and ventral abdominal wall of a preserved cadaver was dissected to identify the muscles and nerves. A unilateral standard TAP block technique was performed (60 mL of methylene blue dye–bupivacaine) on a fresh cadaver in right lateral recumbency. A modified subcostal technique was performed on the opposite side using a linear ultrasound transducer and in-plane approach. Injection points (two 30 mL dye) were at the level of the TAP (between the rectus abdominis and transversus abdominis muscles and ventral to the cutaneous trunci muscle) perpendicular to: 1) the mid-point between the xiphoid cartilage and umbilical scar; and 2) at a point between the caudal and middle thirds of the abdomen measured from the first injection point to the umbilical scar. The modified subcostal approach was performed in seven additional cadavers in both hemiabdomens, with three cadavers in lateral and four cadavers in dorsal recumbency. Ultrasound guidance was used with all injections. Results: The standard approach stained the sixteenth to eighteenth thoracic nerves (T16–T18). The modified subcostal approach performed in lateral recumbency provided greater spread (T9–T17) than dorsal recumbency (T12–T18) ( p = 0.016). Conclusions and clinical relevance: The modified subcostal TAP approach resulted in extensive staining exceeding the standard approach. The nerves stained are consistent with production of ventral abdominal wall anesthesia in horses. Clinical studies are needed to verify these findings.